Respiratory syncytial virus: an overview of infection biology and vaccination strategies. (May 2017) - Shafique, Muhammad; Rasool, Muhammad Hidayat; Khurshid, Mohsin
Respiratory syncytial virus (RSV) is the foremost cause of lower respiratory tract infections, especially in infants and young children. To date, there is no licensed vaccine available for RSV. Only option to restrain RSV is a prophylactic treatment in the form of monoclonal antibody (palivizumab). However, it is quite expensive and used in few patients with co-morbidities. In ongoing research, virologists contemplate about various vaccine candidates to control RSV infection. This review will help in understating the RSV pathobiology and encompass the advancement on various vaccine candidates that would lead to reduce the incidence, mortality and morbidity. Furthermore, it will lighten up the different avenues which might be useful for the development of novel vaccination approaches.